FORMULASI DAN EVALUASI SEDIAAN LIP BALM KOMBINASI MINYAK ALPUKAT DAN EKSTRAK UMBI BIT MERAH (Beta vulgaris L.) - Suciati, Anugerah; Marfu'ah, Nurul; Sawitri, Satwika Budi; Widyaratna, Indriyanti; Mahmudah, Amalia Nurul (JFM (Jurnal Farmasi Malahayati), 2025)
Lip balm is one of the cosmetic products applied to the lips to maintain healthy lips so that they remain moist and add aesthetic value. Avocado oil contains palmitic acid, linoleic acid, and sterolin which can be used as a moisturizer in lip balm preparations. Avocado oil can be combined with beetroot extract which has betacyanin compounds to reduce black color on the lips so that the lips become brighter. This study aims to make a lip balm combination of avocado oil and red beetroot extract and conduct a physical evaluation test of the preparation. The research method used is experimental. The results of the study showed that the results of the organoleptic test of the lip balm preparation combination of avocado oil and red beetroot extract showed a red to dark red color, a distinctive sweet smell and a soft texture. The pH test is 4.5-8.0, the spreadability test is 5-7cm, the power test is >4 seconds, the melting point test is 50-51℃, all formulations are homogeneous and do not cause irritation. The formulation of a lip balm preparation combining avocado oil and red beetroot extract that produces a preparation with the best characteristics is F1 with a concentration of 15% avocado oil and 10% red beetroot extract with stable pH values, adhesive power, and spreadability after stability testing.